Mercury-Tolerant Ensifer medicae Strains Display High Mercuric Reductase Activity and a Protective Effect on Nitrogen Fixation in Medicago truncatula Nodules Under Mercury Stress - Arregui, Gabriela; Hipólito, Pablo; Pallol, Beatriz; Lara-Dampier, Victoria; García-Rodríguez, Diego; Varela, Higinio P.; Tavakoli Zaniani, Parinaz; Balomenos, Dimitrios; Paape, Timothy; Coba de la Peña, Teodoro; Lucas, M. Mercedes; Pueyo, José J. (Frontiers in Plant Science, 2021)
Mercury (Hg) is extremely toxic for all living organisms. Hg-tolerant symbiotic rhizobia have the potential to increase legume tolerance, and to our knowledge, the mechanisms underlying Hg tolerance in rhizobia have not been investigated to date. Rhizobial strains of Ensifer medicae, Rhizobium leguminosarum bv. trifolii and Bradyrhizobium canariense previously isolated from severely Hg-contaminated soils showed different levels of Hg tolerance. The ability of the strains to reduce mercury Hg2+ to Hg0, a volatile and less toxic form of mercury, was assessed using a Hg volatilization assay. In general, tolerant strains displayed high mercuric reductase activity, which appeared to be inducible in some strains when grown at a sub-lethal HgCl2 concentration. A strong correlation between Hg tolerance and mercuric reductase activity was observed for E. medicae strains, whereas this was not the case for the B. canariense strains, suggesting that additional Hg tolerance mechanisms could be playing a role in B. canariense. Transcript abundance from merA, the gene that encodes mercuric reductase, was quantified in tolerant and sensitive E. medicae and R. leguminosarum strains. Tolerant strains presented higher merA expression than sensitive ones, and an increase in transcript abundance was observed for some strains when bacteria were grown in the presence of a sub-lethal HgCl2 concentration. These results suggest a regulation of mercuric reductase in rhizobia. Expression of merA genes and mercuric reductase activity were confirmed in Medicago truncatula nodules formed by a sensitive or a tolerant E. medicae strain. Transcript accumulation in nodules formed by the tolerant strain increased when Hg stress was applied, while a significant decrease in expression occurred upon stress application in nodules formed by the Hg-sensitive strain. The effect of Hg stress on nitrogen fixation was evaluated, and in our experimental conditions, nitrogenase activity was not affected in nodules formed by the tolerant strain, while a significant decrease in activity was observed in nodules elicited by the Hg-sensitive bacteria. Our results suggest that the combination of tolerant legumes with tolerant rhizobia constitutes a potentially powerful tool in the bioremediation of Hg-contaminated soils.